The shape of resilience; A framework for integrating the regenerative production of localized food and energy within an urban community - Bay, Joo (Earthscan from Routledge, 2017)
As the interconnected forces of Modernist planning polices, over consumption and climate change (both anthropomorphic and naturally occurring) increase the frequency and magnitude of shocks to the optimal function of modern centrally planned cities. The inability of these cities to mitigate, adapt to and efficiently recover from these shocks will become more prevalent. This vulnerability is born out of a systemic conception of an urban environment as a centrally defined paradigm, over a large and ever expanding area. This chapter discusses a proposal for a decentralized and self-organized urban framework, which explores the ability of decentralization and self-organization, as an urban morphology, to adapt to rapid changes, at both macro and local scales, through a theoretical case study for Perth, Western Australia. It demonstrates a contextual and resilient restructuring of the systematic make-up of a low density, sprawling urban environment that allows for the production of food and energy and the collection and treatment of waste water to be integrated with and driven by civil society.